(untitled) - Capras, Deborah (Thành phố Hồ Chí Minh, 2014)
Collins Small Talk gives you the confidence to start a conversation and transition into bigger conversation topics so that you are able to build relationships, develop business partnerships and be successful in business.
Keywords: English language,Tiếng Anh; Business English,Tiếng Anh thương mại